KORELASI KEKUATAN OTOT TUNGKAI DAN PANJANG TUNGKAI TERHADAP FREKUENSI TENDANGAN LURUS SISWA PUTRA PESERTA EKSTRAKURIKULER PENCAK SILAT SMP PGRI 1 DENPASAR TAHUN PELAJARAN 2018/2019 - Dei, Agustinus (Widyadari : Jurnal Pendidikan, 2019)
Constraints that are dominant in the field, there are various characteristics and abilities of students such as leg muscle strength and leg length, erratic health conditions and lack of talent and interest in children towards the martial arts sports especially in kick techniques. The purpose of this study was to determine the correlation of limb muscle strength and leg length to the frequency of students' straight kicks of male participants in the PGRI 1 Denpasar Junior High School Pencak Silat Extracurricular Year 2018/2019. The population in this study amounted to 62 people. Of these, 30 were taken as samples according to inclusion, exclusion and group out criteria. This research was carried out in the Pencak Silat Padepokan of SMP PGRI 1 Denpasar for two days. The measurement test given is a measurement of the length of the leg with an antrophometer in units of cm. Data collected through tests and measurements and analyzed using statistical analysis using the multiple correlation formula.           Based on the analysis of the calculation of the normality test of the results of the limb muscle strength test with normal distribution (Fkolmogorov-Smirnov = 0.113; p> 0.05 and VShapiro-Wilk = 0.974; p> 0.05). For leg length data results are normally distributed (FFkolmogorov-Smirnov = 0.120; p> 0.05 and FShapiro-Wilk = 0.978; p> 0.05). Likewise for data from the number of straight kicks normally distributed (Fkolmogorov-Smirnov = 0.154; p> 0.05 and Fkolmogorov-Smirnov = 0.967; p> 0.05). For homogeneity test shows a statistical value of 0.531 and a significance number of 0.593 (p> 0.05) has the same or homogeneous variant. The value of the multiple correlation (R) in this study was 0.878 in a very strong level. The coefficient of determination (KP) is 77.09 ° 0 and the remaining 22.91% are other factors not examined in this study. Significance level = 0.05% and db = 28 test Fh = 4.54 greater than Ft = 3.34 (Fh> Ft) which means the correlation in this study is significant.          Based on the data analysis, it can be concluded that there is a correlation between limb muscle strength and limb length to the frequency of students' straight kicks of male participants of the PGRI 1 Denpasar Junior High School Pencak Silat extracurricular 2018/2019, so that the null hypothesis tested is rejected and the alternative hypothesis in this study is accepted.